2018
DOI: 10.1007/s00244-017-0501-y
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and Sublethal Effects of the Herbicide Atrazine in the Early Stages of Development of Physalaemus gracilis (Anura: Leptodactylidae)

Abstract: Water sources used as reproductive sites by crying frog, Physalaemus gracilis, are extensively associated with agroecosystems in which the herbicide atrazine is employed. To evaluate the lethal and sublethal effects of atrazine commercial formulation, acute and chronic toxicity tests were performed in the embryonic phase and the beginning of the larval phase of P. gracilis. Tests were started on stage 19 of Gosner (Herpetologica 16:183-190, 1960) and performed in 24-well cell culture plates. Acute tests had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 35 publications
0
8
0
2
Order By: Relevance
“…Studies on different frog species exposed to atrazine concentrations up to 20 μg L −1 (exposure periods from 2 to 75 days) have indicated that there are no significant effects on embryo hatchability and tadpole growth i.e length and mass endpoints (Allran and Karasov, 2001;Diana et al, 2000;Morgan, 1996) and exposures up to 100 μg L −1 for 75 days do not significantly affect sexual differentiation and survival (Kloas et al, 2009). Studies by Brodeur et al (2009) and Rutkoski et al (2018) have indicated that pre-and prometamorphosis tadpoles are more sensitive to atrazine than embryos. Design flaws and contamination of controls in some studies have led to questionable results and pronouncement of controversial conclusions (Hayes, 2004;Rohr and McCoy, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on different frog species exposed to atrazine concentrations up to 20 μg L −1 (exposure periods from 2 to 75 days) have indicated that there are no significant effects on embryo hatchability and tadpole growth i.e length and mass endpoints (Allran and Karasov, 2001;Diana et al, 2000;Morgan, 1996) and exposures up to 100 μg L −1 for 75 days do not significantly affect sexual differentiation and survival (Kloas et al, 2009). Studies by Brodeur et al (2009) and Rutkoski et al (2018) have indicated that pre-and prometamorphosis tadpoles are more sensitive to atrazine than embryos. Design flaws and contamination of controls in some studies have led to questionable results and pronouncement of controversial conclusions (Hayes, 2004;Rohr and McCoy, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The total length (mm; snout to tail) and body mass (g) of these tadpoles were measured using digital calipers and a precision balance, respectively. Malformations of the oral structures (denticles or general morphology) and the intestine (edemas or general morphology) were evaluated according to Rutkoski et al 70 , 97 . Digital images of the oral and intestine structures were obtained using a digital camera (P510, Nikon, Tokyo, Japan) and analyzed in comparison with the control, using a stereomicroscope (SZ51, Olympus, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…There were several new studies that included mortality as part of their assessment for fish and amphibians ( Figure 5). The frog Physalaemus gracilis was exposed to atrazine as the formulated product under laboratory conditions for 96 h with a reported LC50 of 229,430 mg/L (score for quality of methods was 2) (Rutkoski et al 2018). As the response was observed at >100 lg/L, the score for relevance was reduced to 0.…”
Section: Survival Of Fish and Amphibians After Short-term Exposures Tmentioning
confidence: 99%
“…No significant differences in overall survival at study termination, survival to metamorphosis, or survival to tail re-absorption were reported. Rutkoski et al (2018) exposed the larvae of Physalaemus gracilis to atrazine as the formulated product for 7 d (score for quality of methods was 2). Stages-19 to -25 were exposed to 16 concentrations (450, 1000, 1700, 8500, 10,000, 25,000, 50,000, 60,000, 70,000, 80,000, 115,000, 125,000, 135,000, 145,000, 155,000, and 165,000 mg/L).…”
Section: Survival Of Fish and Amphibians After Long-term Exposures Tomentioning
confidence: 99%
See 1 more Smart Citation